Simultaneous analysis of twenty-six mycotoxins in durum wheat grain from Italy - Juan, C.; Covarelli, Lorenzo; Beccari, G.; Colasante, V.; Mañes, J. (Pergamon, 2016)
© 2015 Elsevier Ltd. A multi-mycotoxin analysis method based on liquid chromatography coupled to triple quadrupole mass spectrometry was validated and applied for the determination of twenty-six mycotoxins, including eight trichothecenes, three fumonisins, sterigmatocystin, ochratoxin A, four aflatoxins, zearalenone, five "emerging" mycotoxins and three Alternaria mycotoxins in 74 durum wheat samples from central Italy. Eighty-eight percent of the analysed samples contained one or more mycotoxins, with enniatin B showing the highest contamination levels (78% of samples with levels ranging from 23 to 1826 ng/g), followed by enniatin B1 (10-1384 ng/g) and deoxynivalenol (48-2267 ng/g). This work gives an important contribution in terms of mycotoxin analysis and occurrence in durum wheat and in assessing the mycotoxicological risk posed by both traditional and emerging mycotoxins for the final consumers of durum wheat derived products.